Bilateral Pseudoarthrodesis: A Case Report of Complex Bilateral Total Knee Replacement for a Severe Hemophilia A Patient with Inhibitors. Issue 1 (January 2022) - Assi, Hussein; Massé, Vincent; Saint-Yves, Hugo; Barry, Janie; St-Louis, Jean; Isler, Marc
Abstract : Case: We present a severe hemophilia A patient with high titers of inhibitors presenting stage IV knee arthropathy with functional bilateral arthrodesis. On presentation, his mode of ambulation was to project himself forward without the benefit of any significant ankle motion. Total knee arthroplasty was performed on both knees and allowed significant improvement in the range of motion of both knees from 5° to 100°. Conclusion: Although hemophilic patients with inhibitors can represent complex cases, successful outcomes can be achieved in a multidisciplinary team setting. However, we would recommend performing this type of surgery at an earlier stage when less extensive muscle and tendon release is required.